Pengaruh Literasi Keuangan, Inovasi Produk dan Harga terhadap Kinerja Keuangan : (Studi Kasus pada UMKM Kuliner di Alun-Alun Sukoharjo) - Bela Tri Widhiastuti; Edi Wibowo; Dorothea Ririn Indriastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to analyze the influence of financial literacy on the financial performance of Culinary MSMEs, product innovation on the financial performance of Culinary MSMEs and price on the financial performance of Culinary MSMEs. This research is a survey of Culinary MSMEs in Alun-alun Sukoharjo. This research used a sample of 100 people with a sampling technique using purposive sampling. Data collection techniques use library research. The data analysis technique uses multiple linear regression analysis methods, t test, f test, and determination test. The research results show that financial literacy has an influence on the financial performance of Culinary MSMEs, product innovation on the financial performance of Culinary MSMEs and price on the financial performance of Culinary MSMEs.